Facile synthesis of hydrazono bis-4-oxothiazolidines. (2nd November 2022) - Mostafa, Sara M.; Aly, Ashraf A.; Bräse, Stefan; Nieger, Martin; Mohamed, Asmaa H.
Abstract : Herein, we reported on a new series of hydrazono bis-4-oxothiazolidines during the reaction of (hydrazinecarbonothioyl)hydrazinecarbothioamides with dimethyl acetylenedicarboxylate in ethanol as a solvent. The products were obtained in good yields. The structure assignment of obtained products was confirmed by NMR, mass and IR spectroscopy in addition to elemental analyses. The structure of the products was also confirmed by a single-crystal X-ray structure analysis. The possible mechanism for the reaction was also discussed. GRAPHICAL ABSTRACT: UF0001